A true long horn—a new species of Macronemus Dejean, 1835 (Coleoptera, Cerambycidae, Lamiinae, Acanthoderini) from the Bolivian Andes - Perger, Robert; Santos-Silva, Antonio (Zootaxa, 2018)
A new species of long-horned beetle, Macronemus waxrasapa sp. nov. from Bolivian Yungas forest, is described and illustrated.